The formation and evolution of flower coloration in Brassica crops - Li, Xuewei; Zheng, Mingmin; Gan, Qingqin; Long, Jiang; Fan, Haiyan; Wang, Xiaoqing; Guan, Zhilin (Frontiers in Genetics, 2024)
The flower coloration of Brassica crops possesses significant application and economic value, making it a research hotspot in the field of genetics and breeding. In recent years, great progress has been made in the research on color variation and creation of Brassica crops. However, the underlying molecular mechanisms and evolutional processes of flower colors are poorly understood. In this paper, we present a comprehensive overview of the mechanism of flower color formation in plants, emphasizing the molecular basis and regulation mechanism of flavonoids and carotenoids. By summarizing the recent advances on the genetic mechanism of flower color formation and regulation in Brassica crops, it is clearly found that carotenoids and anthocyanins are major pigments for flower color diversity of Brassica crops. Meantime, we also explore the relationship between the emergence of white flowers and the genetic evolution of Brassica chromosomes, and analyze the innovation and multiple utilization of Brassica crops with colorful flowers. This review aims to provide theoretical support for genetic improvements in flower color, enhancing the economic value and aesthetic appeal of Brassica crops.